2006
DOI: 10.1111/j.1365-2826.2006.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Pretreatment Enhances Angiontensin II‐Induced Neuronal Excitation But Not Salt Drinking in Male Fischer Rats

Abstract: Central administration of angiotensin (Ang) II stimulates thirst and sodium intake via the AT-1 receptor. Mineralocorticoid pretreatment enhances Ang II-induced drinking of hypertonic salt solutions (i.e. the synergy theory) in Wistar and Sprague-Dawley rats. Electrophysiological experiments using iontophoretic application of Ang II, and the AT-1 receptor specific nonpeptide antagonist losartan, have shown excitation of neurones in the preoptic/medial septum region of urethane anaesthetised male Wistar rats. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Numerous in vitro and in vivo studies have demonstrated a direct role of Aldo in the development of cardiovascular disease via oxidative stress (11,36,43,48). Long-term administration of an NADPH oxidase inhibitor, apocynin, in the drinking water to deoxycorticosterone acetate (DOCA)-salt rats significantly decreased systolic BP and superoxide production in aortic rings compared with that of rats treated with DOCA-salt alone (1).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous in vitro and in vivo studies have demonstrated a direct role of Aldo in the development of cardiovascular disease via oxidative stress (11,36,43,48). Long-term administration of an NADPH oxidase inhibitor, apocynin, in the drinking water to deoxycorticosterone acetate (DOCA)-salt rats significantly decreased systolic BP and superoxide production in aortic rings compared with that of rats treated with DOCA-salt alone (1).…”
mentioning
confidence: 97%
“…Recently, it has been shown that Aldo significantly increased the number and expression of AT 1 Rs and ACEs in the brain (63,64). Mineralocorticoid pretreatment can enhance ANG IIinduced neuronal excitation in the preoptic/medial septum region (36). However, there have been few studies investigating the central interactions between ANG II and Aldo.…”
mentioning
confidence: 98%
“…In a subsequent study on Fischer rats, again looking at behavior of both the intact, non-anesthetized animal and neurons in the forebrain of anesthetized animals, it was observed that DOCA pretreatment could increase the responsiveness of forebrain neurons to AngII, as reported previously in Wistar rats, but that the salt drinking responses to centrally applied AngII were not enhanced (23). Thus, the two phenomena can be separated and perhaps enhancement can be observed depending on the degree of increased excitability, or degree of decreased inhibition, of the forebrain neurons.…”
mentioning
confidence: 74%